Boogsie, Robbie Create Pure Magic - Blood, Peter Ray (Guardian)
The Ministry of Planning and Sustainable Development to commemorate the 50th anniversary of independence staged the event, Pure Magic where revered pannists Len "Boogsie" Sharpe and his counterpart Robbie Greenidge headlined the show. The audience was treated to a varied repertoire and the performances included numerous original compositions.
Keywords: Musicians -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Music -- Performance -- Trinidad and Tobago